Transformation of Public Administration in the Digital Era - А. A. Likhtin (Управленческое консультирование)
The purpose of the article is to characterize the conditions for the transformation of pub- lic administration in the digital age. The relevance of the research is connected with the actively spreading digital innovations, which increasingly cover the frontiers of public ad- ministration, forming a new framework for institutional changes. These changes need competent reflection and systematization. The theoretical part of the work is devoted to the discussion of the concepts of “open government”, “digital government”, “digital trans- formation”, which have become one of the key elements of public management discourse. The process of digitalization involves the free flow of information from public authorities to the public and third parties, such as civil society organizations and the media, as well as from the public and third parties to the authorities, and is at the heart of well-function- ing open governments that are successfully undergoing the path of digital transformation. Methodologically, the article is based on expert interviews with representatives of public authorities of St. Petersburg, aimed at forming an idea of the institutional framework for the transformation of public administration in the context of digitalization. The author of the article conducted a number of expert interviews with the deputy heads of the districts of St. Petersburg and the deputy chairmen of the committees. As a method of interview analysis, the content analysis of the interview was used using the software ATLAS.ti 9 (http://atlasti.com). The main procedures implemented in this program are coding and grouping by category. As a result of the study, 16 codes were identified, which were com- bined into 3 semantic categories: macro-institutional conditions, micro-institutional condi- tions, and technical conditions for successful transformation of public administration in the context of digitalization. Analyzing the interview data, the author comes to the conclusion that the success of the transformation of public administration in the era of digitalization is directly related to the efforts and resources allocated by public sector bodies to imple- ment the law or policy, both at the time of implementation and over time. In other words, the interweaving of macroinstitutional, microinstitutional, and technical conditions plays a critical role. At the same time, the competencies of civil servants at all levels of govern- ment are a unifying element, a generative factor in the implementation of both macro-in- stitutional, micro-institutional, and technical conditions for the transformation of public administration in the era of digitalization.